Religious Group Cues and Citizen Policy Attitudes in the United States - Adkins, Todd (Politics and religion, 2013)
The public opinion literature shows that cues about the policy positions of social groups influence citizens' political attitudes. We assess whether cues about religious groups' positions affect attitudes on three issues: protection of homosexuals in the workplace, improving the socio-economic conditions of African-Americans, and government-provided health insurance. We argue that such cues should shape issue attitudes and condition the impact of religious and political orientations on those attitudes. That should be especially true on issues closely connected to religion and for citizens with low levels of political awareness. We assess this argument with a survey experiment pitting pairs of religious groups on opposite sides of issues. We find that religious group cues matter primarily for cultural attitudes, among less politically-aware individuals, and for the religiously unaffiliated, Democrats, and liberals. The dominant effect is negative, moving these groups away from the positions of religious leaders and especially evangelical leaders.